2011
DOI: 10.1182/blood-2010-08-303354
|View full text |Cite
|
Sign up to set email alerts
|

Combination anti-CD74 (milatuzumab) and anti-CD20 (rituximab) monoclonal antibody therapy has in vitro and in vivo activity in mantle cell lymphoma

Abstract: Mantle cell lymphoma (MCL) is an aggressive B-cell malignancy with a median survival of 3 years despite chemoimmu-notherapy. Rituximab, a chimeric anti-CD20 monoclonal antibody (mAb), has shown only modest activity as single agent in MCL. The humanized mAb milatu-zumab targets CD74, an integral membrane protein linked with promotion of B-cell growth and survival, and has shown preclinical activity against B-cell malig-nancies. Because rituximab and milatu-zumab target distinct antigens and potentially signal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 50 publications
2
78
0
Order By: Relevance
“…ICBP90 also may provide a functional link that will increase our understanding of MIF's role in the inflammatory pathogenesis of human tumors (52,53), especially with emerging data suggesting associations between high expression MIF alleles and tumor progression (14,54). Finally, given ongoing efforts to develop MIF-based therapies, which may be most beneficial in high MIF expressors, the present findings open the possibility of the pharmacological targeting of ICBP90 in immunological and oncologic disease (19,40,55 EMSAs. Nuclear extracts from human THP-1 monocytes were analyzed with the LightShift Chemiluminescent EMSA Kit (Thermo Scientific).…”
Section: Discussionmentioning
confidence: 99%
“…ICBP90 also may provide a functional link that will increase our understanding of MIF's role in the inflammatory pathogenesis of human tumors (52,53), especially with emerging data suggesting associations between high expression MIF alleles and tumor progression (14,54). Finally, given ongoing efforts to develop MIF-based therapies, which may be most beneficial in high MIF expressors, the present findings open the possibility of the pharmacological targeting of ICBP90 in immunological and oncologic disease (19,40,55 EMSAs. Nuclear extracts from human THP-1 monocytes were analyzed with the LightShift Chemiluminescent EMSA Kit (Thermo Scientific).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been observed with the combination of rituximab and milatuzumab in the presence of a crosslinking Ab in MCL lines. 17 Our studies also indicate that the induction of HA by the anti-CD20/CD74 HexAbs can be blocked without affecting the sustained activation of ERKs and JNK, and neither classic apoptosis nor autophagy is involved in the resulting cell death, which appeared to closely resemble the actin-and lysosome-dependent cell death evoked by tositumomab and hL243 in Raji and SU-DHL4. 49 The present data also indicate that 20-(74)-(74), but not 74- (20)- (20), is internalized into JeKo-1; 74- (20)- (20) However, this advantage is lost in the xenograft model, which may be because of ADCC and CDC activity.…”
Section: Discussionmentioning
confidence: 75%
“…We have previously noted 20 that one effective approach to converting a type I anti-CD20 mAb to a type II can be achieved by making the type I mAb multivalent, as shown by the HexAb generated from the type I veltuzumab, 20- (20)- (20), which exhibits biologic properties attributable to both type II (eg, weak CDC; negative for calcium mobilization; positive for antiproliferation, apoptosis, and HA) and type I (eg, positive for trafficking to lipid rafts). 20 The strategy to target both CD20 and CD74 with distinct mAbs was reported recently by us in a preclinical study that used a combination of milatuzumab and rituximab plus a crosslinking Ab in MCL lines and primary tumor cells, 17 which showed that the treatment resulted in rapid cell death, generation of ROS, loss of ⌬ m , strong HA, and inhibition of p65 nuclear translocation. The observed cell death was attributed to a nonclassical apoptotic mechanism, because it lacked evidence of autophagy and caspaseactivation but required the participation of actin and lysosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of anti-MIF and -CD74 antibodies, with the objective that therapeutic intervention may be guided by an individual's MIF genotype (28)(29)(30).…”
mentioning
confidence: 99%